2013
DOI: 10.1037/a0032449
|View full text |Cite
|
Sign up to set email alerts
|

Contrast negation and the importance of the eye region for holistic representations of facial identity.

Abstract: Reversing the luminance values of a face (contrast negation) is known to disrupt recognition. However, the effects of contrast negation are attenuated in chimeric images, in which the eye region is returned to positive contrast (S. Gilad, M. Meng, & P. Sinha, 2009, Role of ordinal contrast relationships in face encoding, Proceedings of the National Academy of Sciences, USA, Vol. 106, pp. 5353-5358). Here, we probe further the importance of the eye region for the representation of facial identity. In the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 41 publications
5
37
0
Order By: Relevance
“…Recent studies have shown that restoring the normal contrast polarity of the eye region while the rest of the face remains contrast-inverted improves recognition performance (Gilad et al, 2009;Sormaz et al, 2013) and can eliminate inversion-related N170 modulations (Gandhi et al, 2012). The present experiment demonstrates that contrast-inversion of the eyes or of the rest of the face can both affect N170 components, depending on which part of a face is fixated.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Recent studies have shown that restoring the normal contrast polarity of the eye region while the rest of the face remains contrast-inverted improves recognition performance (Gilad et al, 2009;Sormaz et al, 2013) and can eliminate inversion-related N170 modulations (Gandhi et al, 2012). The present experiment demonstrates that contrast-inversion of the eyes or of the rest of the face can both affect N170 components, depending on which part of a face is fixated.…”
Section: Discussionmentioning
confidence: 60%
“…Inverting the contrast of the eyes should therefore have a greater effect on face processing than contrast inversions of other parts of a face, in particular when eye gaze is directed towards its preferred position near the eye region. Gilad, Meng, and Sinha (2009) explored this hypothesis with "contrast chimera" faces, which include both contrast-inverted and contrast-normal regions, and demonstrated that restoring only the eye region of a contrast-inverted face to positive contrast improved recognition performance to approximately 90% of the level observed with contrast-normal faces (see also Sormaz, Andrews, & Young, 2013). They also showed that fMRI activity in the fusiform face area elicited by these positive-eyes chimeras was indistinguishable from the response to contrast-normal faces.…”
Section: Introductionmentioning
confidence: 99%
“…Because the eye region contains several important contrast-related signals (e.g. the boundaries between the sclera, iris and pupil of the eye, and contrast differences between the eyes and surrounding regions including eyebrows), inverting the contrast polarity of this region is particularly detrimental for face recognition, and restoring this region to normal contrast eyes in an otherwise contrast-inverted face leads to dramatic improvements in recognition performance (Gilad et al, 2009;Gandhi et al, 2012;Sormaz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These images were generated by selectively inverting the contrast of the eye region within an otherwise normal-contrast face (negative-eyes chimeras) or by leaving the eye region unchanged and contrast-inverting the rest of the face (positive-eyes chimeras; see Figure 1A). Previous studies have shown that restoring 7 the normal contrast of the eye region in an otherwise contrast-inverted face improved face recognition to approximately 90% of the level observed for normal-contrast faces (Gilad et al, 2009;Sormaz, Andrews, & Young, 2013), and also strongly reduced the effects of contrast inversion on the N170 component (Fisher, Towler, & Eimer, 2015;Gandhi, Suresh, & Sinha, 2012). Such observations demonstrate that contrast signals from the eye region are particularly important during early perceptual stages of face processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation